Exploring Translation Strategies Of Arabic Subtitles On Sexual Taboos In The English Drama Series “sex Education” - Alnusairat, Suhib Ahmad Saleh (2024)
Audio-visual translation, particularly subtitling, has drawn the attention of various scholars. However, the audiovisual translation of Arabic subtitles is rare. This descriptive study aims to investigate the translation of sexual taboo language in Arabic subtitles to determine how subtitlers translate English sexual taboos into Arabic. The present study also assesses whether these taboo sexual expressions have been reinforced, maintained, or downplayed in the Arabic subtitles. Additionally, the study analyzes how subtitlers deal with sexual expressions that do not have equivalents in the target language and builds a glossary for the sexual taboo terms to find their equivalents in Arabic. This study focuses primarily on eight groups of sexual taboos: masturbation, orgasms, oral sex, homosexuality, menstruation, prostitution, genital organs, and copulation, which are based on Allan and Burridge’s (2006) categorization of sexual taboos. The definition of transferring strategies here was adopted from a combination of the works of Díaz-Cintas and Remael (2007), Pedersen (2011), and Flotow (1997). The Skopos theory (1984), polysystem theory (1978/2000), and manipulation theory (1985) were used to form the theoretical framework of the study. Santaemilia (2008) underlines the need to research the translation of sex-related language because it is a sensitive and privileged issue where researchers may confront cultural, moral, and ethical limitations and also find a balance between conveying the source meaning and preserving culture and ideology. Two seasons of the British series Sex Education form the corpus of the study.